Optimizing coal ash as a sustainable substitute of cement and aggregate in structural concrete - Fahad-ul-Rehman Abro,; Abdul Salam Buller,; Tariq Ali,; Imran Ali Channa,; Zain-ul-Abdin,; Safeer Ahmad Zaheer, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The manufacture of concrete for constructing the structures like highways, bridges, and buildings requires large amounts of cement and aggregates. This high concrete production depletes natural resources like sand and gravel for the construction industry. It also negatively impacts the environment due to cement usage. This study looked at using waste materials like coal bottom ash (CBA) and fly ash (FA) in concrete as substitutes for some of the typical aggregates and cement. The goal was to reduce the environmental impact and preserve natural resources. The study made concrete with regular Portland cement, sand, 10mm coarse aggregate, locally available CBA, and FA. 15% fly ash was selected as an optimal level from initial testing. The CBA was used to replace 0-35% of the fine aggregate sand. Test cubes and cylinders were made with different mixes. Compressive strength, tensile strength, carbonation, and sulfate attack tests were done after curing. Results showed 25% CBA improved the concrete’s mechanical performance. The compressive and tensile strengths increased but not above conventional concrete. This is because CBA needs more moisture for full hydration over longer curing times. Also, the concrete’s durability improved in terms of resistance to carbonation and sulfate attack.